The Rauer-Rengali connection in the Indo-Antarctica amalgam: Evidence from structure, metamorphism and geochronology - Sawant, A.; Gupta, S.; Clark, Christopher; Misra, S. (Geological Society Publishing House, 2017)
© 2017 The Author(s). India and East Antarctica collided during assembly of the Rodinia supercontinent at around 1 Ga. Granulites related to this orogeny are exposed in the Eastern Ghats Province (EGP) in India, and these are believed to have been contiguous with granulites of the Rayner Province in East Antarctica at that time. In the Indian segment, we describe a shear zone between the EGP and the Rengali Province to its north along which strongly foliated bands of garnetiferous quartzofeldspathic gneisses, khondalites and charnockites are intercalated. The foliation is consistently east-west trending and subvertical, with downdip intersection lineations. Maximum asymmetry in horizontal sections and textural analysis using electron backscattered diffraction (EBSD) analysis confirm that the transport vector during shearing was horizontal. The shear zone is interpreted as a dextral strike-slip fault that operated under greenschist-facies conditions, juxtaposing 1 Ga EGP granulites with 2.8 Ga cratonic granulites to the north. The corresponding region in East Antarctica is represented by the Rauer Group, where intercalations between 2.8 and 1.0 Ga, vertically orientated lithologies, are observed alongside 0.5 Ga shear zones. These features in the Rauer Group can be correlated with those in the Rengali Province, further supporting existing palaeogeographical reconstructions of Gondwana.